Radiative association for the formation of phosphorus monochloryl cation (PCl+) and aluminium monochloride (AlCl) - Chen, Yang; Lin, Xiaohe; Xiao, Lidan; Li, Zijian; Zhang, Songbin; Cheng, Yongjun; Wu, Yong; Almeida, Amaury A. de; Andreazza, Carmen M. [UNESP]; Yan, Bing (Oxford Univ Press, 2024)
Cross-sections and rate coefficients for the radiative association processes of Al(P-2) with Cl(P-2) for the formation of aluminium monochloride (AlCl) and P+(P-3) with Cl(P-2) to form phosphorus monochloryl cation (PCl+) have been estimated as a function of temperature. Rate coefficients have been estimated from cross-sections, which are calculated using a quantum mechanical method. They are found to vary from 4.95 x 10(-21) to 4.24 x 10(-16) and from 7.10 x 10(-18) to 3.50 x 10(-17) cm(3) s(-1) for AlCl and PCl+, respectively, for temperatures ranging from 10 to 15 000 K. The obtained rate constants are fitted with the Arrhenius-Kooij functions for incorporation into astrochemical reaction data bases.
Keywords: astroparticle physics; molecular data; molecular processes; radiation: dynamics; radiation mechanisms: thermal